Primary analysis of repeat elements of the Asian seabass (Lates calcarifer) transcriptome and genome - Kuznetsova, Inna S.; Thevasagayam, Natascha M.; Sridatta, Prakki S. R.; Komissarov, Aleksey S.; Saju, Jolly M.; Ngoh, Si Y.; Jiang, Junhui; Shen, Xueyan; Orbán, László (Frontiers in Genetics, 2014)
As part of our Asian seabass genome project, we are generating an inventory of repeat elements in the genome and transcriptome. The karyotype showed a diploid number of 2n=24 chromosomes with a variable number of B-chromosomes. The transcriptome and genome of Asian seabass were searched for repetitive elements with experimental and bioinformatics tools. Six different types of repeats constituting 8-14% of the genome were characterized. Repetitive elements were clustered in the pericentromeric heterochromatin of all chromosomes, but some of them were preferentially accumulated in pretelomeric and pericentromeric regions of several chromosomes pairs and have chromosomes specific arrangement. From the dispersed class of fish-specific non-LTR retrotransposon elements Rex1 and MAUI-like repeats were analyzed. They were wide-spread both in the genome and transcriptome, accumulated on the pericentromeric and peritelomeric areas of all chromosomes. Every analyzed repeat was represented in the Asian seabass transcriptome, some showed differential expression between the gonads. The other group of repeats analyzed belongs to the rRNA multigene family. FISH signal for 5S rDNA was located on a single pair of chromosomes, whereas that for 18S rDNA was found on two pairs. A BAC-derived contig containing rDNA was sequenced and assembled into a scaffold containing incomplete fragments of 18S rDNA. Their assembly and chromosomal position revealed that this part of Asian seabass genome is extremely rich in repeats containing evolutionally conserved and novel sequences. In summary, transcriptome assemblies and cDNA data are suitable for the identification of repetitive DNA from unknown genomes and for comparative investigation of conserved elements between teleosts and other vertebrates.